New Imidazole-Based N-Phenylbenzamide Derivatives as Potential Anticancer Agents: Key Computational Insights - Malik, M. Shaheer; Alsantali, Reem I.; Jamal, Qazi Mohammad Sajid; Seddigi, Zaki S.; Morad, Moataz; Alsharif, Meshari A.; Hussein, Essam M.; Jassas, Rabab S.; Al-Rooqi, Munirah M.; Abduljaleel, Zainularifeen; Babalgith, Ahmed O.; Altass, Hatem M.; et al. (Frontiers in Chemistry, 2022)
An efficient atom economical synthetic protocol to access new imidazole-based N-phenylbenzamide derivatives is described. A one-pot three-component reaction was utilized to provide a series of N-phenylbenzamide derivatives in a short reaction time (2-4 h) in 80-85% yield. The cytotoxic evaluation revealed that derivatives, 4e and 4f, exhibited good activity with IC50 values between 7.5-11.1 M against the tested cancer cell lines. Computational studies revealed interesting insights, the docking of the active derivatives (4e and 4f) showed a higher affinity towards the target receptor protein than the control. Molecular dynamic simulations revealed that the active derivatives form stable complexes with ABL1-kinase protein. Moreover, the ADME and drug likeness of the derivatives reinforced the potential of the derivative to be taken up for further development as anticancer agents.